Gender Issues in Child Labor - World Bank (World Bank, Washington, DC, 2012)
This note reviews the available evidence on developing effective policies against child labor, outlining it requires attention to gender differences among working children. This is so because standard definitions of child labor tend to underestimate girls' work, because economic activities of boys and girls differ by country and industry; because determinants of child labor may differ by gender; and, because the consequences of child labor may differ by gender. A number of policy implications stem from evidence presented in this note, i.e., that including time use modules in household surveys would capture unpaid household chores performed by children, thereby providing more accurate estimates of total work time; interventions to reduce child labor should address its specific causes, and should recognize that these causes may differ by gender. The determinants of child labor should be examined by running separate regressions for boys and girls, or by interacting the gender dummy, with the main explanatory variables. Furthermore, investing in water infrastructure, providing low-cost child care, and increasing access to health care facilities can significantly reduce the time that girls spend on household chores, thereby increasing their school attendance. Finally, interventions aimed directly at increasing children's schooling-such as providing subsidies for school fees, reducing distance to schools, and improving school quality-are also likely to reduce the prevalence of child labor.